Trends in incidence and complications of ankle arthrodesis and total ankle arthroplasty - Pottanat, Paul J.; Burnett, Zachary; Kamalapathy, Pramod; Park, Joseph; Werner, Brian (International Journal of Research in Orthopaedics, 2024)
Background: Total ankle arthroplasty (TAA) and ankle arthrodesis (AA) are surgical treatment options for end-stage ankle arthritis. Providers should have a current understanding of the overall trends of these procedures as both are frequently used. Thus, the objective of the current study is to assess the trends in utilization, patient characteristics and outcomes after TAA and AA. Methods: The PearlDiver Mariner database was used to capture patient characteristics and outcomes related to 2,494 patients who underwent TAA and 5,901 patients who underwent AA between 2010 and 2018. Results: The incidence of TAA increased over the course of the study period (p<0.001) while the incidence of AA decreased (p=0.045). Length of stay (LOS) following AA significantly increased (3.02 vs 4.50, p<0.001) while LOS following TAA significantly decreased (2.78 vs 1.65, p=0.004). Furthermore, incidence of infections significantly increased following both procedures (AA 1.7% vs 6.6%, p=0.004; TAA 0.8% vs 2.7%, p=0.008). In 2018, patients who underwent TAA had a significantly decreased LOS (1.65 vs 4.50, p<0.001), risk of major complications (1.5% vs 3.9%, p=0.042), risk of any medical complication (7.1% vs 14.9%, p=0.004), and risk of infection (2.7% vs 6.6%, p=0.011) compared to those who underwent AA. Conclusions: The present study demonstrates increased utilization of TAA for treatment of end-stage ankle arthritis compared to AA in recent years. Over the time period of this study, infection rates have increased and LOS has decreased for TAA while both infection rate and LOS have increased for AA.